If it's not what You are looking for type in the equation solver your own equation and let us solve it.
3x+14=4x-26
We move all terms to the left:
3x+14-(4x-26)=0
We get rid of parentheses
3x-4x+26+14=0
We add all the numbers together, and all the variables
-1x+40=0
We move all terms containing x to the left, all other terms to the right
-x=-40
x=-40/-1
x=+40
| 12(9x+3)=1008 | | 6.3r=45.36 | | 85z −18=824−2z | | a+21=-9 | | 8(2^x*3)=48 | | 14=-8m | | z+45=33 | | 7x=30-2 | | 7y−1=3y+11 | | 11x-9/3-10=3 | | 14n=n | | x/6-9=5 | | 7x/6-12=156 | | 15+p=-12 | | 3.25=2.5+r | | 15n-6.5=53.3 | | 15x/8+7=37 | | x/8=15/23 | | 90x=80x+75 | | w/14=6 | | 8+3(4x-6)=9-5(2x+1) | | 5c+3(8–c)=36 | | 7^3x-5=7(1-x) | | 52x=40x+60 | | 6(4x-8)-8=6(x-4)+58 | | 7x+45=9x+2 | | 2x+31-x=9+5x-6 | | x+26=39x | | -8w-22=-5(w+5) | | h-3.5=9h | | 9x=6x-24 | | m+3m+m-35=180 |